2019
DOI: 10.1002/jso.25462
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting recurrence after complete resection for thymic epithelial tumors based on the TNM classification: A multi‐institutional retrospective analysis

Abstract: Objectives This study aimed to compare the predictive ability between the Masaoka‐Koga (M‐K) staging system and the 8th TNM staging system for the recurrence of thymic epithelial tumors (TETs). In addition, a nomogram was developed on the basis of the proposed TNM classification to predict individual recurrence rate. Methods A retrospective study was performed on 445 patients who underwent complete resection (R0) of TETs between January 2000 and February 2013. Concordance index (C‐index) was used as a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our univariate Cox analysis showed that the TNM stage was a significant independent risk factor for 1-year HCC recurrence. The predictive ability of the TNM stage for tumor recurrence has already been assessed in several types of cancer, such as eyelid carcinoma [25], thymic epithelial tumors [26] and lung cancer [27], and a model has been established combining the TNM stage and tumor size to predict recurrence among HCC patients [28]. However, the AUC of the TNM stage to predict 1-year recurrence in our study demonstrated low predictive efficacy.…”
Section: Discussionmentioning
confidence: 69%
“…Our univariate Cox analysis showed that the TNM stage was a significant independent risk factor for 1-year HCC recurrence. The predictive ability of the TNM stage for tumor recurrence has already been assessed in several types of cancer, such as eyelid carcinoma [25], thymic epithelial tumors [26] and lung cancer [27], and a model has been established combining the TNM stage and tumor size to predict recurrence among HCC patients [28]. However, the AUC of the TNM stage to predict 1-year recurrence in our study demonstrated low predictive efficacy.…”
Section: Discussionmentioning
confidence: 69%
“…In this study analysis, the number of stage II patients was too small to be statistically analyzed and the TNM stage was not observed to be a strong prognostic factor in multivariable Cox analysis. However, another study based on the KART database showed that the TNM staging system was superior to the M-K staging system in terms of FFR [ 10 ]. There were statistically significant differences in OS between stage I and stage III and between stage I and stage IV (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the importance of clinicopathological features as predictive factors for survival outcomes, including age, 27,28 tumor length/diameter, 5,18 tumor stage, 10,29 and WHO type. 7,29 Therefore, novel parameters have been explored to achieve a clear understanding of the prognostic factors of TETs and improve survival outcomes. 8,9,30 In this present study, we first reported that the pathological tumor L/S ratio was a prognostic factor for survival outcomes in TETs.…”
Section: Discussionmentioning
confidence: 99%